Determination of Grapevine Leafroll Diseases Infection in Turkey - Yağmur Türkmen; Filiz Ertunç (Turkish Journal of Agriculture: Food Science and Technology)
During the growing seasons between 2009 and 2010, totally 213 shoot and leaf samples were collected from the vineyards in Manisa, Denizli, Nevşehir, Elazığ, İzmir, Ankara, Çanakkale, Tekirdağ, Edirne and Kırklareli, which are commercially important viticulture production areas of Turkey. All grapevine samples were serologically investigated for the presence of Grapevine leafroll-associated viruses (GLRaVs) using GLRaV-1, GLRaV-2, GLRaV-3, GLRaV 4-9, GLRaV-6 and GLRaV-7 DAS-ELISA kits. In 143 of total, (67.14%) single or multiple infections were detected. GLRaV4-9, -7, -3, -1, -2 and -6 were detected as 53.52%, 36.15%, 34.74%, 32. 86%, 32.39% and 3.28%, respectively in the surveyed area. Eastern Anatolia Region had the highest infection rate (100%), followed by Marmara, Aegean, and Central Anatolia Region (69.74%, 75%, 62% and 26.47%, respectively). While the highest infection rates were obtained in Marmara Region for GLRaV-1, -2 and -3 as 43.42%, 44.74% and 50% respectively, GLRaV4-9 found as 100% in Eastern Anatolia Region. The highest infection rate was detected in Marmara Region for GLRaV-6 as 3.95%. The most common multiple infection was determined as GLRaV-1, -2, -3, 4-9 and -7 with the rate of 36.17%.